(untitled) (Journal SCIENCEVOLUTION, 2024)
The special feature presents a study through the Valley of a Thousand Flowers from Narsarsuaq, the Kujata area, a corner of the world with historical and natural value in Greenland. This valley became a protected area after being declared a World Heritage Site by UNESCO (United Nations Educational, Scientific and Cultural Organization). The microscopic image sampling focuses on lichens, mosses and flowers, which is the main vegetation of the Nordic area studied. It should be noted that this research represents the first scientific dissemination of these findings in a specialized journal. It also highlights the importance of the subarctic landscape of Kujataa, which combines agriculture, grazing, and hunting of marine mammals, which is one of the few places where it is legal to consume whales and seals.